Clinical Experience with High-Dose Polymyxin B against Carbapenem-Resistant Gram-Negative Bacterial Infections—A Cohort Study - Yiying Cai; Hui Leck; Ray W. Tan; Jocelyn Q. Teo; Tze-Peng Lim; Winnie Lee; Maciej Piotr Chlebicki; Andrea L. Kwa (Antibiotics, 2020)
Population pharmacokinetic studies have suggested that high polymyxin B (PMB) doses (≥30,000 IU/kg/day) can improve bacterial kill in carbapenem-resistant Gram-negative bacteria (CR-GNB). We aim to describe the efficacy and nephrotoxicity of patients with CR-GNB infections prescribed high-dose PMB. A single-centre cohort study was conducted from 2013 to 2016 on septic patients with CR-GNB infection and prescribed high-dose PMB (~30,000 IU/kg/day) for ≥72 h. Study outcomes included 30-day mortality and acute kidney injury (AKI) development. Factors associated with AKI were identified using multivariable regression. Forty-three patients with 58 CR-GNB received high-dose PMB; 57/58 (98.3%) CR-GNB were susceptible to PMB. The median daily dose and duration of high-dose PMB were 32,051 IU/kg/day (IQR, 29,340–34,884 IU/kg/day) and 14 days (IQR, 7–28 days), respectively. Thirty-day mortality was observed in 7 (16.3%) patients. AKI was observed in 25 (58.1%) patients with a median onset of 8 days (IQR, 6–13 days). Higher daily PMB dose (aOR,1.01; 95% CI, 1.00–1.02) and higher number of concurrent nephrotoxins (aOR, 2.14; 95% CI; 1.03–4.45) were independently associated with AKI. We observed that a sizable proportion developed AKI in CR-GNB patients described high-dose PMB; hence, the potential benefits must be weighed against increased AKI risk. Concurrent nephrotoxins should be avoided to reduce nephrotoxicity.